Hubungan Kebersihan Diri dengan Kejadian Diare pada Petugas Kebersihan Tempat Pembuangan Akhir Bakung Bandar Lampung - Agung Satria Utama H; Dyah Wulan Sumekar; Sofyan Musyabiq Wijaya (CV. Jasa Sukses Abadi, 2020)
Personal hygiene means the act of maintaining one's personal hygiene and health for their physical and psychological well-being. Personal hygiene is one of the factors that can increase the risk of diarrhea. Janitors are a group of workers who have a high risk of experiencing health problems because of continuous exposure to garbage. The objective is to identify the relation of personal hygiene with diarrhea occurrence at janitor in Bakung landfills Bandar Lampung. The design of this survey is the analytical method with a cross-sectional approach to 58 respondents. This study used a questionnaire to assess the respondent’s personal hygiene and the incidence of diarrhea. The data obtained were calculated using the Chi-square test. Out of 58 participants, 40 participants (69%) were found to have good personal hygiene and 18 participants (31%) were found poor personal hygiene, while 24 participants (41,4%) were found experienced diarrhea and 34 (58,6%) were found did not experience diarrhea. Chi-square test result showed that there was a correlation between personal hygiene and diarrhea occurrence with a p-value of 0,02 (p<0,05). The findings in this study can be understood as there was a correlation between personal hygiene and diarrhea occurrence at janitor in Bakung landfills Bandar Lampung.